Special exits a graphic memoir - Farmer, Joyce 1938- (Fantagraphics Books, 2010)
A graphic memoir chronicling the decline of the authors elderly parents health, their relationship with one another and with their daughter, and how they cope with the day-to-day fragility of the most taxing time of their lives
Keywords: Farmer, Joyce -- 1938- -- Family -- Comic books, strips, etc; Graphic novels; Underground comics; Married people -- California -- Los Angeles -- Comic books, strips, etc; Older people -- California -- Los Angeles -- Comic books, strips, etc; Parent and child -- Comic books, strips, etc; Comic